Fully Digital Workflow for Planning Static Guided Implant Surgery: A Prospective Accuracy Study - Lin, Chia-Cheng (J Clin Med, 2020)
The accuracy of static guided implant surgery (sGIS) using conventional planning workflow has been extensively examined; however, more information is required to justify the application of fully digital planning protocol. The purpose of this study was to investigate the clinical accuracy of sGIS with a fully digital planning workflow. Twenty-one partially edentulous patients were enrolled in this prospective study. Cone-beam computed tomography (CBCT) and intraoral scans were taken and superimposed by matching the dental surface images directly (surface registration protocol) or by matching fiducial markers on a stereolithographic (SLA) radiographic template fabricated from the digital data of the intraoral scan (fiducial marker registration protocol). Virtual implant treatment plans were then determined, and tooth-supported SLA surgical guides were fabricated according to the plans. Twenty-six implant surgeries were performed via the surgical guide by one surgeon. Pre- and post-operative CBCT images were superimposed, and the positional and angular deviations between placed and planned implants were measured with metrology software. A total of 43 fully guided implants were placed, in which 25 implants were planned with the surface registration protocol. Implants planned based on the surface registration protocol had a larger mean angular deviation than the fiducial marker registration protocol. No significant differences were found for any deviations of the examined variables. Within the limits of this study, we concluded that the clinical accuracy of the sGIS planned with a fully digital workflow was consistent with the conventional workflow for partially edentulous patients.